Analysis on IPO Underpricing of Homebound Cross-listed Chinese A-shares Compared to Domestic A-shares (2006-2014) - ZHU, LINGYAO (2015)
This paper provides analysis on the IPO underpricing of homebound cross-listed IPOs compared to domestic IPOs in China. By investigating the market adjusted initial return of a total sample of 1205 observations, which includes 1165 A-shares and 40 homebound A-H shares during 2006-2014, we find that the phenomenon of IPO underpricing is still prevailing for homebound cross-listed IPOs.